Impact of platelet transfusion refractoriness in the first 30 days post-hematopoietic stem cell transplantation on outcomes of patients with myelodysplastic syndrome - Zhang, Yuanfeng; Wang, Yan; Ma, Runzhi; Liu, Li; Sun, Jiali; Chen, Xin; Yang, Donglin; Pang, Aiming; Zhang, Rongli; Ma, Qiaoling; Zhai, Weihua; He, Yi; et al. (Frontiers in Immunology, 2024)
In this study, we performed a myelodysplastic syndrome (MDS)-specific retrospective analysis to determine whether platelet transfusion refractoriness (PTR) in one-month post-HSCT in patients with MDS could influence outcomes. Among the 315 patients enrolled, 110 (34.9 %) had PTR from stem cell infusion to one-month post-HSCT. Baseline characteristics of the PTR and non-PTR groups were similar. We found that patients with PTR had a slower and lower rate of platelet engraftment by day 28, as well as a slower recovery of neutrophils. The median days of neutrophil and platelet engraftment were 14 days (9-23) and 17 days (8-28) in the PTR groups versus 13 days (9-23) and 15 days (7-28) in the non-PTR group (P<0.001). By day 28, 84 of 110 patients (76.4%) with PTR achieved platelet engraftment compared with 181 of 205 patients (88.3%) without PTR achieving platelet engraftment (P=0.007). In addition, patients in the PTR group received significantly more red blood cell (median, 17 units vs. 10 units, P<0.001) and platelet transfusions (median, 13 units vs. 7 units, P<0.001). However, the overall survival was similar between the two groups. PTR in one-month post-HSCT, haploidentical donor, and ferritin level>1041ng/ml (median level) were independent adverse factors of platelet engraftment.